KEWENANGAN KEUCHIK DALAM PENERBITAN SURAT KETERANGAN TANAH DALAM PERSPEKTIF SIYASAH IDARIYAH - Geunta Farabi Yuzka; Misran Misran; Bustamam Usman (Journal of Indonesian Comparative of Syari'ah Law, 2025)
With a focus on the decision of the Administrative Court (PTUN) Banda Aceh Number 25/G/2024/PTUN.BNA from the perspective of fiqh siyasah idariyyah. The main issue raised is the abuse of authority by the keuchik who issued an SKT beyond his jurisdiction, resulting in land ownership disputes and legal uncertainty for the community. The research method employed is normative-juridical with statutory, case, and conceptual approaches. The findings show that the PTUN Banda Aceh decision serves as both an administrative correction and judicial oversight of the keuchik’s actions. From the perspective of fiqh siyasah idariyyah, the ruling reflects the implementation of the principles of justice (al-ʿadālah), public interest (al-maṣlaḥah al-ʿāmmah), and the specialization of functions (takhṣīṣ al-wazīfah). By annulling the legally flawed SKT, the court not only protects the rights of aggrieved individuals but also strengthens village governance toward greater accountability and compliance with good governance principles. In conclusion, the integration of Indonesian positive law and the values of fiqh siyasah idariyyah provides an essential foundation to prevent the misuse of authority at the village level and to safeguard justice and public welfare.